Hubungan Pengetahuan dan Sikap Keluarga dengan Tingkat Kepulihan Pasien ODGJ yang Dirawat di Rumah Wilayah Kerja Puskesmas Sendana I Tahun 2025 - Aisyah, Nur; Pattola, Pattola; Afni, Nur; Immawanti, Immawanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
Mental disorders remain a serious health problem because they can affect patients’ social functioning, emotional condition, and quality of life. In the recovery process of People with Mental Disorders (PMD), family plays an important role as the main support system through their knowledge and attitudes toward patient care. This study aimed to determine the relationship between family knowledge and attitudes with the recovery level of PMD patients treated at home in the working area of Sendana I Public Health Center. This study used a quantitative analytic design with a cross-sectional approach. The sample consisted of 34 respondents selected using the Slovin formula. Data were collected using questionnaires and analyzed using Fisher’s Exact Test with a significance level of α=0.05. The results showed that most respondents had poor knowledge, accounting for 20 respondents (58.8%), while 26 respondents (76.5%) had positive attitudes. Most patients had a low recovery level, accounting for 13 respondents (38.2%). Statistical analysis showed a significant relationship between family knowledge and the recovery level of PMD patients with p=0.001, and a significant relationship between family attitudes and the recovery level of PMD patients with p=0.001. This study concludes that better family knowledge and more positive family attitudes are associated with better recovery levels among PMD patients treated at home